(untitled) (Research, Society and Development, 2021)
This article carried out an analysis of the Covid-19 pandemic in order to verify its correlation with the increase in vulnerabilities. Thus, bibliographic and documentary research was methodologically used from a qualitative approach. The main objective of the analysis was to categorize vulnerabilities and perform the imbrications of the pandemic with this category, inscribed in the capitalist mode of production from its neoliberal direction. As specific objectives, this research aimed to identify the most vulnerable groups affected by the health crisis. In this sense, it was possible to observe as results that the pandemic affects with greater force the most vulnerable and impoverished groups of the population around the world, that is, the pandemic does not have the same effect for all. The study concludes by presenting as possible ways out of the pandemic crisis the overcoming of the capitalist mode of production, the weakening of the right, the strengthening of the state and the greater participation of the community.